Determinants of Corrupt Economy: A Tobit Regression Analysis on G20 Countries in the 2012-2021 Period - Permana, Andre Sukma; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2025)
This study aims to analyze the economic determinants of corruption in G20 member countries. Some of the economic factors that are thought to be the cause of corruption based on the author's literature review are GDP per capita, economic growth, inflation, and economic freedom. The data used in this study are annual data from 2012-2021 taken from the World Bank report and Heritage.org. The analysis technique used is Tobit regression with the help of the STATA version 17.0 program as the main research software to process the data of the research variables. The results showed that simultaneously (simultaneously) the independent variable of economic freedom had a significant and positive effect, while the variables of GDP per capita, economic growth, and inflation had an insignificant effect on the probability of corruption levels in the G20 member countries in 2012-2021.